2020
DOI: 10.21037/tp-20-110
|View full text |Cite
|
Sign up to set email alerts
|

A term neonate with early myoclonic encephalopathy caused by RARS2 gene variants: a case report

Abstract: The RARS2 gene encodes mitochondrial arginine-tRNA synthetase. Patients with variants of the RARS2 gene have pontocerebellar hypoplasia type 6 (PCH6), which is characterized by early onset seizures, progressive microcephaly, and developmental delay. PCH6 is a rare mitochondrial encephalopathy.To the best of our knowledge, the onset seizure type which the ictal video-electroencephalogram (VEEG) was compatible with early myoclonic encephalopathy (EME) has not been reported. Here we reported a term female neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Since it was first reported by Edvardson et al 6 . in 2007, around 30 cases have been reported, 7 few of which were from China 8,9 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since it was first reported by Edvardson et al 6 . in 2007, around 30 cases have been reported, 7 few of which were from China 8,9 …”
Section: Discussionmentioning
confidence: 96%
“…5 Since it was first reported by Edvardson et al 6 in 2007, around 30 cases have been reported, 7 few of which were from China. 8,9 Patients with RARS2 mutations are more likely to develop symptoms within 3 months of birth. Initial symptoms include seizures, hypotonia, difficulty feeding, dyspnea, and hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we describe two children with a new RARS2 phenotype that is quite distinct from the previously described early infantile developmental and epileptic encephalopathy RARS2 phenotype. In the 15 published cases that describe the RARS2 epilepsy phenotype in detail, [2][3][4][5][6][7][8][9][10][11][12] seizure onset occurred by 3 months in the setting of abnormal development. In contrast, our children presented with a progressive movement disorder at 8 and 9 months on a background of normal development.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our cases with the epileptology reported for RARS2 encephalopathy; adequate information was only available for 15/52 reported cases (Table 1). [2][3][4][5][6][7][8][9][10][11] 3 | RESULTS…”
Section: Methodsmentioning
confidence: 99%